The semantic field 'salvation' in Paul's major epistles : a componential analysis of his soteriological metaphors - Van Deventer, H. J. (Hendrik Jakobus), 1953- (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1986.